Geologische Karte/Geological Map 1:25 000 Hanssonhorna (10° 12' W 74° 21' S) Heimefrontfjella, Antarktis - Bauer; W.; Spaeth; G.: Lehr- und Forschungsgebiet Geologie; Endogene Dynamik der RWTH Aachen (DE); Jacobs, J.; Weber, K.; Siegesmund, S.: Institut für Geologie und Dynamik der Lithosphäre, Göttingen (DE); Thomas; R. J.: Council for Geoscience; Belville (ZA) (Alfred-Wegener-Institut, Bremerhaven, Institut für Geologie und Dynamik der Lithosphäre, Universität Göttingen and Bundesamt für Kartographie und Geodäsie, Frankfurt am Main, 1998)
Geological Map, Geological field work in 1985/86; Topography and Contour lines derived from stereophotogrammetric mapping of an Aerial survey flight on 2 January 1986; Ground control and spot heights taken from Norwegian map series Dronning Maud Land 1:250 000 and German GPS surveying in 1985/86; Inset maps: Location diagram, Geographical names diagram, Index to adjoining sheets; Reliability data, Geological terms, Sources of English, Norwegian and German place-names, see map legend; Series of 15 Geological Maps of Heimefrontfjella at 1:25 000 scale: Vikenegga, Hanssonhorna, Bjørnnutane, Gramkroken, Scharffenbergbotnen, Furubotnnabben, Sirinuten, Monsrudnabben, Norumnuten, Ryghnuten, Kvitebotnen, Juckeskammen, Cottontoppen, Wordsfoldfjellet; Scale: 1:25000; Projection: Lambert Conformal Conic; Bounding Box: POLYGON ((-10.2 -74.35, -9.65 -74.35, -9.65 -74.4667, -10.2 -74.4667, -10.2 -74.35)); Datum: WGS72